2010
DOI: 10.1002/hep.23809
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Outcomes in Hepatitis C–Infected Patients with Varying Degrees of Virologic Response to Interferon-Based Treatments

Abstract: Patients with chronic hepatitis C with partial virologic response or nonresponse to interferon‐based therapies can experience treatment‐related improvements in liver histology. This retrospective analysis assessed the histologic response to treatment in patients with varying degrees of virologic response (sustained virologic response [SVR], breakthrough, relapse, or nonresponse), time to hepatitis C virus (HCV) RNA undetectability, and duration of viral suppression. Patients (HCV genotypes 1‐6) with baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…This finding is in agreement with the finding of [34] who demonstrated that serum AST levels < 40 U/l is correlated independently with complete response. Pockros et al [35] demonstrated that there is no significant difference in ALT level between responders and non-responders.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is in agreement with the finding of [34] who demonstrated that serum AST levels < 40 U/l is correlated independently with complete response. Pockros et al [35] demonstrated that there is no significant difference in ALT level between responders and non-responders.…”
Section: Discussionmentioning
confidence: 98%
“…14 A significant regression of fibrosis has been observed previously among hepatitis B patients after long-term virologic suppression with tenofovir disoproxil fumate. 23 Although the exact mechanism is unclear, suppression of viral replication may reduce hepatic inflammation and consequent fibrosis, allowing regeneration of healthy tissue.…”
Section: Discussionmentioning
confidence: 78%
“…However, even in the absence of SVR treatment, benefits have been observed. Both reduction in portal pressure [20] and significant histological improvement with antiviral therapy have been observed in the absence of achievement of SVR [21]. This observation is supported by studies in animal models where type 1 interferons have been shown to have a direct antifibrotic effect [22,23].…”
Section: Introductionmentioning
confidence: 72%